PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGGULANGI HUMAN TRAFFICKING TERHADAP PEKERJA MIGRAN INDONESIA PERIODE 2016 - 2020 - Dovana Hasiana, (2022)
Indonesia is a sending, a transit, and a destination country for human trafficking. Each province in Indonesia acts not only as a place of origin but also as a transit area and destination for the crime. Human trafficking in Indonesia is closely related to Indonesian Migrant Workers, where Indonesian Migrant Workers are vulnerable to human trafficking and which leads them to be sent abroad and be exploited. However, the Indonesian Government's efforts in handling human trafficking have not been maximized, this can be proven through Indonesia's Tier 2 status in the Human Trafficking Report for the 2016 - 2020 period. The theoretical framework used to develop the analysis in this research is International Organizations, Roles, and Human Trafficking. The method used in this research is qualitative using the case study method. In conclusion, IOM has significant roles in playing its role sets as a supporting role for the government and the role of coordinator among stakeholders. IOM also plays its role as an instrument of Indonesia, an independent actor with its own decisions and policies, and as an arena for facilitating cooperation.